Нові для України види копрофільних аскоміцетів. I. Піреноміцети та локулоаскоміцети - Голубцова, Ю.І. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Сообщается о восьми новых для Украины видах копрофильных пиреномицетов и локулоаскомицетов, собранных в Новгород-Сиверском Полесье в 2004—2005 гг. Sporormiella australis (Speg.) S.I. Ahmed et Cain, S. minimoides S.I. Ahmed et Cain, S. vexans (Auersw.) S.I. Ahmed et Cain и Trichodelitschia bisporula (P. Crouan et H. Crouan) Munk — представители порядка Pleosporales, а Coniochaeta scatigena (Berk. et Broome) Cain, Podospora setosa (G. Winter) Niessl, Schizothecium aloides (Fuckel) N. Lundq. и Sch. vesticola (Berk. et Broome) N. Lundq. — Sordariales. Для всех таксонов представлены подробные описания, иллюстрации, синонимы и местонахождение в Украине. Обсуждаются особенности их морфологии и общего распространения. Eight species of coprophilous pyrenomycetes and loculoascomycetes new for Ukraine are recorded in 2004—2005 in Novgorod-Sivers’k Polissia (Chernigov and Sumy regions). Sporormiella australis (Speg.) S.I. Ahmed et Cain, S. minimoides S.I. Ahmed et Cain, S. vexans (Auersw.) S.I. Ahmed et Cain, and Trichodelitschia bisporula (P. Crouan et H. Crouan) Munk belong to the order Pleosporales, Coniochaeta scatigena (Berk. et Broome) Cain, Podospora setosa (G. Winter) Niessl, Schizothecium aloides (Fuckel) N. Lundq., and Sch. vesticola (Berk. et Broome) N. Lundq. are representatives of the order Sordariales. Descriptions, illustrations, synonyms and localities in Ukraine are provided for each taxon. Characters of their morphology and general distribution are discussed.